Updating The Subject Literacy of the Teacher as A Necessity for Improving His Professional Competence - G. M., Kussainov (2021)
The article shows the need to update the subject literacy of a teacher to improve his professional competence. The concept of subject literacy, its role and place in improving the professional competence of both a teacher and improving the quality of teaching schoolchildren are revealed.